PUTUSAN HAKIM BERUPA PEMIDANAAN PERKARA TINDAK PIDANA PERBUATAN CABUL TERHADAP ANAK DIBAWAH UMUR - Anis Mohamad (Universitas Islam Darul Ulum, 2018)
This criminal morality of minors is not new, and this criminal act has obtained a place of regulation in the Criminal Code , which is set forth in the Second Book of Chapter XIV on